2009
DOI: 10.1080/02640410903352923
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training on resistin, leptin, cytokines, and muscle force in elderly post-menopausal women

Abstract: It may be that resistance exercise can be used to prevent the degenerative processes and inflammation associated with ageing. Thus, the aim of the present study was to evaluate the effects of resistance training on cytokines, leptin, resistin, and muscle strength in post-menopausal women. Thirty-five sedentary women (mean age 63.18 years, s = 4.8; height 1.64 m, s = 0.07; body mass 57.84 kg, s = 7.70) were recruited. The 16 weeks of periodized resistance training consisted of two weekly sessions of three sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
1
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 42 publications
5
91
1
12
Order By: Relevance
“…However, this study demonstrated a 13, 47, and 14 % increment with an ES of 0.56 (small), 0.96 (small), and 0.74 (small) for the same exercises. One can hypothesize that these differences would be attributed to a higher variability within subjects in this study as compared with the study of Prestes et al (2009c).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…However, this study demonstrated a 13, 47, and 14 % increment with an ES of 0.56 (small), 0.96 (small), and 0.74 (small) for the same exercises. One can hypothesize that these differences would be attributed to a higher variability within subjects in this study as compared with the study of Prestes et al (2009c).…”
Section: Discussionmentioning
confidence: 76%
“…A previous study using the same LP scheme and older women (Prestes et al 2009c) revealed a significant increase in bench press, 45°leg press, and standing arm curl strength after 16 weeks of RT. When comparing the delta increment and effect size (ES), the study of Prestes et al (2009c) demonstrated a 22, 29, and 9 % increment with an ES of 1.25 (moderate), 8.96 (large), and 4.42 (large) for bench press, 45°leg press, and standing arm curl, respectively. However, this study demonstrated a 13, 47, and 14 % increment with an ES of 0.56 (small), 0.96 (small), and 0.74 (small) for the same exercises.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations